ICT Adoption and Its Role in Enterprise Innovativeness: The Cases of Medium and Large Manufacturing Industries in Adama City, Ethiopia - Ali, Tayu Woldegiorgis; Ahmed, Abdi Yuya (CV. Literasi Indonesia, 2024)
The purpose of this study was to gain a deeper understanding of the effects of information communication technology adoption on the innovativeness of medium and large-size manufacturing industries in Adama City, Ethiopia. The study employed a qualitative multiple-case study approach, interviewing top managers from five purposefully selected companies. Semi-structured interviews were used for in-depth discussions, and the data was analyzed using a cross-case analysis technique to identify common themes across all companies. The research findings revealed that information communication technology adoption supports the manufacturing industries by increasing production speed, enabling product promotion, performing online orders, and improving communication and organizational work structure. However, adoption is hindered by internal issues like unskilled workers, uncommitted managers, reluctant investors, financial limitations, and external challenges such as supply shortages, expensive equipment, poor education and policy systems, political instability, and lack of international payment options like PayPal and credit card bank services. Despite supporting innovation, information and communication technology used in manufacturing remains limited due to internal and external factors. The study recommends increased awareness training and government action on infrastructure, policy, and education to improve information and communication technology adoption.